The Native American Mascot Controversy: A Handbook - King, C. Richard (Rowman & Littlefield Publishers, 2010)
Sports mascots have been a tradition for decades. Along with the usual lions and tigers, many schools are represented by Native American images. Once considered a benign practice, numerous studies have proved just the opposite: that the use of Native American mascots in educational institutions has perpetuated a shameful history of racial insensitivity. The Native American Mascot Controversy provides an overview of the issues that have been associated with this topic for the past 40 years. The book provides a comprehensive and critical account of the issues surrounding the controversy, explicating the importance of anti-Indian racism in education and how it might be challenged. A collection of important primary documents and an extensive list of resources for further study are also included. Expounding the dangers and damages associated with their continued use, The Native American Mascot Controversy is a useful guide for anyone with an interest in race relations.